Expression Profile of Apoptotic Genes Bak1 and Bcl2 in Pakistani Presbycusis Patients from Faisalabad and Chichawatni Populations - Abdul Rauf; Rashid Bhatti; Saleeha Kausar; Sehar Aslam; Nazia Nahid; Muhammad Qasim (Journal of Liaquat University of Medical & Health Sciences, 2024)
Objective: To analyze the expression profiles of two apoptotic genes, BAK1 and BCL2, in Pakistani ARHI patients’ blood samples compared to healthy subjects. Methodology: This expression profiles study was conducted at the Sight Centre of Bahawalpur City of Southern Punjab from August 2022 to July 2023. All of the subjects were from Faisalabad or Chichawatni, Pakistan cities. The participants exposed to head injury or trauma, noise exposure, ototoxic medication, chemical exposure, diabetes, liver cirrhosis, neurological disease, psychiatric disease, cognitive dysfunction, middle ear disease, and brain tumour factors were excluded from the study. Individuals with cold or flu were also excluded from the study. RNA was extracted from both the peripheral blood samples of healthy and affected individuals. The quantity of RNA was then determined, and cDNA was synthesized from it. This cDNA was then utilized in qPCR to assess the relative expression of the BAK1, BCL2, and ACTB genes using gene-specific primers. Results: Our results suggested that ARHI patients had higher levels of BAK1 expression and BAK1/BCL2 ratio than healthy subjects. Conclusion: Thus, apoptosis mediated by BAK1 may be a key mechanism controlling the development of ARHI. Furthermore, changes in BAK1 gene expression of blood samples might be utilized as a rapid test for early diagnosis of ARHI.